INVENTARISASI HUKUM PERKAWINAN DAN LARANGAN PERKAWINAN KELOMPOK HAKKA STUDI MARGA LIU,KWAN,CONG DI KABUPATEN KUBU RAYA - NIM. A1011211012, ARIE STIGUEL (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractThis study examines the norm of intermarriage prohibition of Liu, Kwan, and Cong clans in the Hakka community in Kubu Raya Regency, West Kalimantan, which is rooted in the